1998
DOI: 10.1093/humrep/13.5.1266
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between open and percutaneous needle biopsies in men with azoospermia

Abstract: Open testicular biopsy is a classic method of investigation in men with azoospermia. Recently, percutaneous needle biopsy of the testis has been used in attempts to obtain material for histopathological diagnosis in such cases and to retrieve spermatozoa for intracytoplasmic sperm injection (ICSI). To determine whether a 19 gauge (G) and a 21G butterfly needle could be used for percutaneous aspiration of testicular tissue to determine the presence of mature spermatids and assess spermatogenesis, 10 patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 19 publications
4
69
0
6
Order By: Relevance
“…Importantly, IVF-ICSI using surgically retrieved spermatozoa is the only method available that allows men with non-obstructive azoospermia (NOA) to father their own genetic offspring [Devroey et al 1995;Silber et al 1996]. The spermatozoa recovery rate in TESE has been shown to range from 40-70% [Mansour et al 1996;Friedler et al 1997;Schlegel et al 1997;Rosenlund et al 1998], and acceptable fertilization and pregnancy rates using testicular spermatozoa from men with NOA have been reported De Croo et al 2000;Mercan et al 2000;Balaban et al 2001]. Among the subgroups of NOA, Giorgetti et al [2005] reported that the fertilization rate was significantly lower when the patient exhibited maturation arrest (MA) as opposed to hypospermatogenesis (HS).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, IVF-ICSI using surgically retrieved spermatozoa is the only method available that allows men with non-obstructive azoospermia (NOA) to father their own genetic offspring [Devroey et al 1995;Silber et al 1996]. The spermatozoa recovery rate in TESE has been shown to range from 40-70% [Mansour et al 1996;Friedler et al 1997;Schlegel et al 1997;Rosenlund et al 1998], and acceptable fertilization and pregnancy rates using testicular spermatozoa from men with NOA have been reported De Croo et al 2000;Mercan et al 2000;Balaban et al 2001]. Among the subgroups of NOA, Giorgetti et al [2005] reported that the fertilization rate was significantly lower when the patient exhibited maturation arrest (MA) as opposed to hypospermatogenesis (HS).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, M-TESE has been increasingly used due to better results in obtaining testicular sperm, when compared to TESE (Devroey et al, 1995;Schlegel and Su, 1997;Schlegel, 1999). Failure to retrieve sperm in non-obstructive azoospermia patients may be as high as 57% of patients (Friedler et al, 1997;Rosenlund et al, 1998;Okada et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There is only one reported complication requiring surgical correction, which was testicular bleeding managed with hemostatic suturing [2,3,[13][14][15][16][17] . Hematomas can occur and tend to reabsorb within 1-4 weeks [8] .…”
Section: Discussionmentioning
confidence: 99%